Toxicological assessment of lemongrass (Cymbopogon nardus L.) liquid waste: Biolarvicides againts the third instar larvae of Aedes aegypti - Putri Pameswari; Khairiza Lubis (Jurnal Biolokus: Jurnal Penelitian Pendidikan Biologi dan Biologi, 2022)
Liquid waste generated from the distillation process of lemongrass (Cymbopogon nardus L.) in a relatively short time will cause a foul odor, ammonia or phosphine that occurs due to the fermentation process. These problems can be minimized by reusing liquid waste of lemongrass (C. nardus L.) into biolarvicides. This study aims to determine the value of Lethal Concentration 50 (LC50) from the liquid waste of lemongrass (C. nardus L.) which can kill the third instar larvae of A. aegypti mosquitoes for 24 hours. The liquid waste of lemongrass (C. nardus L.) used in this study is waste obtained from the lemongrass (C. nardus L.) distillery located on Jalan Masjid Ulayat, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra. A total of 10 mosquito larvae of A. aegypti instar III were used for each different concentration of 6,982%, 7,607%, 8,287%, 9,027% and 9,833%. Each concentration consisted of five repetitions and was observed for 24 hours. After 24 hours, larvae that died were analyzed using probit analysis via SPSS 25. The results showed that the LC50 of lemongrass (C. nardus L.) liquid waste can kill larvae for 24 hours was 8,763%.